Small Bowel Transplantation: Current Clinical Status - David Sigalet (Canadian Journal of Gastroenterology)
With recent refinements in immunosuppression techniques, the first successful reports of small bowel transplantation in humans have now been made, increasing interest in bowel transplantation among clinicians and patients alike. This article reviews recent developments in understanding of the functional capabilities and requirements for effective immune suppression in bowel transplantation. Both experimental and clinical experience with transplantation are discussed, as are the areas which appear to offer the most promise for future developments. Finally guidelines for consideration of patient selection for this procedure are reviewed.